Determining Selected Prime Agriculture Commodities through Three Methods - ANWAR, Chairil; MAPPATOBA, Marhawati; HM, Syamsuddin; TAQWA, Edhi (Journal of Environmental Management and Tourism; Vol 12 No 3 (2021): JEMT Volume XII Issue 3(51) Summer 2021, 2021)
Local governments should be able to take pay attention to plan action in efficient way in developing economy of the regency, in order to optimise the economic advantages in the region and to encourage local economic growth. For this purpose, it should be considered to design development planning through selecting sub-sectors and prime products in further design plan of action for the region. This research aims to determine selective prime commodities and sub sector potential through three methods which areas: 1) Location Quotient Analysis, 2) Analytical Hierarchy Process (AHP) 3) Exponential Comparation Method /MPE. The results show that the plantation sub-sector is selected as sector basis of the economy with the value of LQ=1,3694 or LQ>1. In line with the plantation subsector which is nominated as the prime subsector in Tolitoli regency with weight priority value of 0.2927, then the cloves product is selected as prime commodity in the Region with the MPE total weight of 13.1416, and this commodity is nominated as commodity basis with the LQ value of 13.5754.